Humic Acid Alleviates Fe Chlorosis in Graminaceous Plants Through Coordinated Fe-Dependent and Fe-Independent Mechanisms - Garnica, Maria; Baigorri, Roberto; San Francisco, Sara; Zamarreño, Angel M.; Garcia-Mina, Jose M. (Frontiers in Plant Science, 2022)
Many studies have shown the close relationship between the beneficial action of soil and sedimentary humic acids on the growth of plants cultivated in calcareous soils and their ability to improve Fe plant nutrition. These results have been ascribed to the humic acid (HA) capability to improve Fe solubility and bioavailability. However, other effects more related to a humic acid action on the specific mechanisms activated in roots of plants under Fe deficiency cannot be ruled out. Although this question has been studied in dicotyledonous plants, in graminaceous plants there are no specific studies. Here we investigate the ability of a humic acid extracted from peat (HA) to improve Fe nutrition in wheat plants cultivated under Fe deficient and sufficient conditions. The results show that HA can improve the physiological status of Fe deficient wheat plants by alleviating some of the deleterious consequences of Fe deficiency on plant development and increasing the plant ability to secrete phytosiderophores to the nutrient solution. This action of HA is associated with increases in the Fe-active pool in leaves that might be related to the mobilization of the Fe complexed by HA resulting from the interaction of HA with the phytosiderophores in the nutrient solution. The Fe translocation from the root to the shoot may be favored by the action of trans-Zeatin Riboside (tZR) since the leaf concentration of this phytohormone was enhanced by HA in Fe deficient plants.